Carrying Capacity: Nitrogen and the Intensification of Irish Pasture Systems, 1945-2007 - Coleman, Gabriel (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2026)
In the second half of the twentieth century, Ireland's pasture-dominated agricultural sector intensified rapidly, causing significant changes to the nation's economy, politics, environment, and rural communities. This thesis takes an environmental history approach to this intensification, examining its relationship to Ireland's postwar policy of economic expansion and the scientific research institutions that translated this policy into agricultural practice. The thesis focuses on the introduction of synthetic nitrogen fertiliser to the Irish pasture, connecting this new source of abundant agricultural energy with the development of Ireland's natural gas network, intensive practices associated with ryegrass and silage-making, the polluting effects of intensive farm operations and creamery waste, and Ireland's place within the global narrative of the Green Revolution. This narrative is contextualised within the larger political and economic history of European integration as well as the development of Irish and European environmental movements and policy in relation to the increasingly severe environmental impacts of the agricultural sector. The thesis takes a ground-up approach to these narratives, combining a material semiotic framing with eco-Marxist and decolonial theory in order to weave the environmental, social, political, and economic elements of Ireland's postwar agricultural intensification into a single narrative.
APPROVED
Keywords: environmental history; history; environmental humanities; agriculture; agricultural history; agricultural pollution; fertiliser; nitrogen; Ireland; Irish agriculture; pasture; fertiliser manufacturing; natural gas; energy history; soil; silage; pollution; environmental governance; Nitrates Directive